1999
DOI: 10.1177/0959353599009003003
|View full text |Cite
|
Sign up to set email alerts
|

Relations of Domination and Movements for Liberation: An Analysis of Power between Groups (Abridged)

Abstract: Erika APFELBAUM For a long time I thought that June 22, 1944 was the date of my birth, and my death (P. Goldman). A DISCONCERTING QUESTION: WHERE HAS ALL THE POWER GONE?This chapter is concerned with analyzing asymmetric power relations between groups. Thus, it will deal with two linked intergroup phenomena, domination and subordination. 1 It will discuss how power processes create, maintain and perpetuate those intergroup relations that involve domination and subordination.Unquestionably, social psychologists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
9

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 0 publications
1
47
0
9
Order By: Relevance
“…We included female as well as male participants in this study because we thought it naive to assume that women are free of the concern of being or appearing sexist. For one, targets of prejudice often internalize the prejudiced beliefs that others hold of them (Apfelbaum, 1979;Jost & Banaji, 1994; Triandis et al, 1982), which means that anti-Black racism can be found among African Americans, and sexism among women. Also, there is little evidence that women differ from men in their desire to avoid being or being seen as sexist-and one might even expect them to be more wary than men of being or appearing sexist.…”
Section: Discussionmentioning
confidence: 99%
“…We included female as well as male participants in this study because we thought it naive to assume that women are free of the concern of being or appearing sexist. For one, targets of prejudice often internalize the prejudiced beliefs that others hold of them (Apfelbaum, 1979;Jost & Banaji, 1994; Triandis et al, 1982), which means that anti-Black racism can be found among African Americans, and sexism among women. Also, there is little evidence that women differ from men in their desire to avoid being or being seen as sexist-and one might even expect them to be more wary than men of being or appearing sexist.…”
Section: Discussionmentioning
confidence: 99%
“…A su vez, el poder se refleja en las opciones conductuales disponibles, independientemente de la identificación. Pero el tipo de relación de los grupos afecta las estrategias de justicia (Morales, 1998;Apfelbaum, 1979;Sachdev y Bourhis, 1991;Bronfenbrenner, 1987;Wiesenfeld, y Revista de Investigación en Psicología -Vol. 20, N° 1.…”
Section: El Poder Y Los Gruposunclassified
“…A distinção entre uma categoria específica, em que o critério classificatório é um marcador colectivo, como é o caso do sexo para as mulheres, e uma catego ria onde a pertença grupai não anula a distintividade individual, constitui uma instância de relações intergrupais que tem merecido particular atenção por par te dos investigadores europeus (Apfelbaum, 1979;Deschamps, 1982). Neste caso, e contrariando os pressupostos do modelo de Bristol (ver Amâncio, 2000, para uma discussão mais detalhada), a distintividade individual e a diferencia ção intergrupos não são dimensões independentes, antes co-variam, pelo me n os no ca so dos m em b ros dos g ru p o s d o m in a n te s, com o m o stro u Lorenzi-Cioldi (1988) num conjunto de estudos que estabeleceram a homologia entre grupos dominantes e dominados e os grupos de sexo.…”
Section: E As Rupturasunclassified